PENGARUH APLIKASI KOMPOS KOTORAN SAPI DAN PAITAN TERHADAP SIFAT KIMIA TANAH DAN PERTUMBUHAN TANAMAN KEDELAI - Putri Alfira Zuraida; Yulia Nuraini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Fertile agricultural land encourages people to carry out agricultural cultivation activities. But in general, it has decreased soil fertility because its managed intensively without recycling of organic matter and has an impact on decreasing soil fertility chemically such as soil organic carbon and pH then leads to low productivity. Soybean is an agricultural product that necessary to develop because the demand for soybean consumption in East Java Province has always increased. However, Indonesia has not been able to fulfil this demand. One of the technology innovations that can be applied to improve soil fertility that has low organic matter and to increasing soybean production by providing input of quality organic fertilizer in the form of compost (Tithonia and Cow Dung). So this research is important to determine the effect of application cow dung compost and tithonia on soil chemical properties, the growth of soybean crops, and the correlations between soil chemical properties and soybean growth. This study used a randomized block design with 6 treatments and 3 replications. The result showed that the application of tithonia and cow dung compost shows a significant effect on soil chemical properties, plant height, and the number of leaves, but didn’t show a significant effect on the number of branches in every observation. Based on the correlation analysis, the results show a positive correlation between soil chemical properties and soybean growth.